Human resource practices accompanying industry 4.0 in European manufacturing industry. Issue 5 (26th February 2021) - Vereycken, Yennef; Ramioul, Monique; Desiere, Sam; Bal, Michiel
Abstract : Purpose: Recent research has shown that the implementation of Industry 4.0 requires companies to (re)adjust their human resource (HR) policies. This article focuses on the relationship between Industry 4.0 and three HR practices: i.e. employee involvement, job design and skill development. Design/methodology/approach: We use data of the European Company Survey (ECS) (2019). This nationally representative survey in the EU28 gathers data on workplace practices among managers from establishments employing at least 10 employees. We focus on 5, 609 establishments in the manufacturing sector. Findings: Firstly, employee involvement shows a strong positive correlation with Industry 4.0, irrespective of the digital technology used, country or firm size. Secondly, weak but significant correlations are found with increasing job complexity and skill development. Research limitations/implications: Research should engage in fine-grained analyses of the alignment between particular digital technologies and their respective HR practices. Practical implications: Our results stress the importance of involving employees during the implementation of Industry 4.0. Originality/value: Despite frequent acknowledgement across Industry 4.0 roadmaps and maturity models, the predictions for HR practices are empirically incomplete and theoretically inconclusive.